STUDI SOSIAL EKONOMI PETANI KERAMBA DI KECAMATAN PAUH KOTA PADANG - Yosi, Yulia; Juita, S.Pd. M.Si, Erna; Farida, Farida (Pendidikan Geografi, 2014)
Â ABSTRACT.Â The purpose of this research is to get the data, process, analyze and discuss of the sosio economic study of farmer cages in district pauh of padang city. This research is a used descriptive. Samples were 62 families collected by total sampling technique . Instrument used in this study was a questionnaire . Data analysis using the percentage formula. Based on the result of data analysis of the obtained result of the research findings that : 1) farmed fish famers in the district of Padang Pauh obtaining venture capital from it own capital. 2) the level of knowledge cage farmers in the district of Padang Pauh weight usually sown seed growers as much as 40-49 gram a day, spreading seed by farmers cage in the morning. 3)the level of production of cage farmers in the district of Padang Pauh preserved fish cage farmers in general is Â one type of fish mujahir any heavy crop production yield obtained as much as 201-300 kg/head. 4) the level of farmers income cages in Padang Pauh subdistrict average is Rp.1,000,000 â 2,000,000 / month in general there cage farmers have additional income. 5) social interaction cage farming community in the district of Padang Pauh that communication among farmers cage very well established farmers never completely feel unrivaled by other farmers.Â